STRATEGI PEMBELAJARAN BERBASIS NEUROSAINS BERBANTUAN APLIKASI WORDWALL DALAM MENGANALISIS DAN MERANCANG SOAL HOTS - Yeni Rostikawati; Alfa Mitri Suhara; Mekar Ismayani (Jurnal Semantik, 2023)
One of the scientific clusters that students must master is the learning science cluster. One of the subjects in the learning science cluster is Evaluation of Indonesian Language Learning. The aim of this course is to equip students with the skills to analyze and design evaluation instruments. The problem found by students is that they still have difficulties in analyzing and designing evaluation instruments based on HOTS (High Order Thinking Skill). The purpose of this study was to find out the syntax of wordwall-assisted Neuroscience-based learning strategies and the responses of IKIP Siliwangi students in analyzing and designing HOTS evaluation instruments in Indonesian Language Learning. The research method used is descriptive qualitative with identification, formulating problems, literature study, determining instruments for data collection in the form of questionnaires, and analyzing data then drawing conclusions. As for the research results based on the results of the questionnaire data, it was obtained an average of 89.4% positive answers chosen by students. This means that wordwall-assisted Neuroscience-based learning strategies can help students analyze and compile HOTS questions by searching, describing, exploring, presenting, processing, comparing, evaluating, and concluding HOTS questions that are compiled.